Desempeño de las empresas de servicios de diseño e ingeniería de la industria aeroespacial en México: un análisis cualitativo comparado - Manzo Martínez, María Aline (Universidad Michoacana de San Nicolás de Hidalgo, 2019)
The purpose of this study is to identify the necessary and sufficient conditions of design and engineering services firms (DESF) of the Mexican aerospace industry. The study is based on the postulates stablished in the theory of the Resource-Based View (RBV). This approach contributes to the understanding of causality between the performance of the firm, on the one hand, and the presence of certain valuable, rare, non-imitable and non-substitutable resources on the other, such as absorptive capacity, innovation capacity, entrepreneurial capacity, research and development activities (R&D) and specialized human resources. This research selected the approach derived from the qualitative comparative analysis (fuzzy-set Qualitative Comparative Analysis, fsQCA) as an appropriate methodological tool to determine the different configurations that lead to the same outcome (a high performance of the firms in this industry). The results obtained show two routes that firms can follow to achieve the desired outcome. The first route shows that is sufficient the joint presence of innovation capacity, entrepreneurial capacity and R&D activities to generate high performance; while the second route shows that even in the absence of absorptive capacity, high performance can be achieved if innovation capacity, entrepreneurial capacity and specialized human resources are jointly present. Another important aspect to be highlighted in this study, is that the five chosen conditions are considered necessary to generate high performance in DESF that belong to the aerospace industry in Mexico, characterized by a high innovative intensity. Finally, it is concluded that R&D activities and entrepreneurial capacity are considered central causal conditions, while the others are considered peripheral causal conditions.

La presente investigación tiene el propósito de identificar las condiciones necesarias y suficientes que generan un alto desempeño en las empresas de servicios de diseño e ingeniería (ESDI) de la industria aeroespacial mexicana. El estudio se sustenta en los postulados que establece la teoría de Resource Based-View (RBV). Este enfoque contribuye a entender la causalidad que existe entre el desempeño de la empresa, por un lado, y la presencia de ciertos recursos valiosos, raros, inimitables e insustituibles (Barney, 1991) por el otro, tales como la capacidad de absorción, la capacidad de innovación, la capacidad emprendedora, las actividades de investigación y desarrollo (I+D) y los recursos humanos especializados. En esta investigación, se seleccionó el enfoque que se deriva del análisis cualitativo comparado (fuzzy-set Qualitative Comparative Analysis, fsQCA), como una herramienta metodológica adecuada para determinar las diferentes configuraciones que llevan a un mismo resultado (un alto desempeño de las empresas en esta industria). Los resultados obtenidos muestran dos rutas que pueden seguir estas empresas para alcanzar el resultado deseado. La primera ruta señala que es suficiente la presencia conjunta de la capacidad de innovación, la capacidad emprendedora y las actividades de I+D para obtener un alto desempeño, mientras que la segunda ruta muestra que aún en ausencia de capacidad de absorción, se puede llegar a tener un alto desempeño si la capacidad de innovación, la capacidad emprendedora y los recursos humanos especializados están presentes de manera conjunta. Otro de los aspectos que se debe resaltar en esta investigación es que las cinco condiciones elegidas son consideradas necesarias para generar un alto desempeño en las ESDI que conforman la industria aeroespacial en México y que se caracterizan por una alta intensidad innovadora. Por último, se concluye que las actividades de I+D y la capacidad emprendedora son consideradas condiciones causales centrales, mientras que las demás son consideradas condiciones causales periféricas.
Instituto de Investigaciones Económicas y Empresariales. Doctorado en Ciencias en Negocios Internacionales
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1492; info:eu-repo/classification/cti/5; ININEE-D-2019-0565; Desempeño de la empresa; Condiciones necesarias y suficientes; fsQCA